Richard Nixon : American politician - Barron, Rachel (Greensboro, N.C. : Morgan Reynolds, 2004)
10 - 12 years
The last press conference -- The early years -- Tricky Dick -- A dog named Checkers -- Second in command -- Two heartbreaking races -- Victory out of chaos -- President Nixon -- A cancer close to the presidency -- The elder statesman.
Includes bibliographical references and index.
Keywords: Nixon, Richard M. -- 1913-; Presidents -- United States; Presidents